Occupational exposure to indoor air pollution among bakery workers in Ethiopia; A comparison of electric and biomass cookstoves. (February 2018) - Downward, George S.; van der Zwaag, Hugo P.; Simons, Leon; Meliefste, Kees; Tefera, Yifokire; Carreon, J. Rosales; Vermeulen, Roel; Smit, Lidwien A.M.
Abstract: The indoor air pollution (IAP) produced by the domestic combustion of solid fuels is responsible for up to 4 million deaths annually, especially among low and middle income countries. Occupational exposure within the food preparation industries of these nations remains underexplored. We investigated occupational exposure to the IAP produced during the commercial production of injera, a staple of the Ethiopian diet, from bakeries in Addis Ababa, Ethiopia. Measurements of PM2.5, black carbon (via the proxy measure PM2.5 absorbance) and CO were collected from 30 bakeries and their employees for an average of 4-h per working day. Measurements were compared between bakeries using biomass and electric cookstoves. Further, the respiratory health data of 35 bakery employees were collected by interview-based questionnaire. Personal exposure to PM2.5 from biomass cookstoves was double that of electric cookstoves (430 μg/m3 vs. 216 μg/m3), black carbon exposure was four times higher among biomass users (67 × 10-5m-1 vs. 15 × 10-5m-1), and CO exposure was twenty times higher among biomass users (22 ppm vs. 1 ppm). Mixed effect models indicated that the number of stoves in use and additional solid fuel usage (e.g. coffee brewing) also contributed to exposure levels. These findings indicate that the use of biomass powered cookstoves during commercial injera production significantly contributes to IAP and self-reported respiratory symptoms. As injera is the staple foodstuff of Ethiopia, a widespread conversion to electric cookstoves is likely to have a significant impact. However, as high levels of IAP were also observed within the electric bakeries, further identification of pollution sources is required. Graphical abstract: Image 1 Highlights: Solid fuels represent a major health burden within low and middle income countries. Relatively little is known regarding occupational exposures in these settings. We measured PM2.5, black carbon, and CO in bakeries in Addis Ababa, Ethiopia. Bakeries using solid fuel had higher values than those with electricity. Employees of solid fuel bakeries were more likely to report respiratory symptoms. Abstract : In this study of occupational exposure to indoor smoke among Ethiopian bakery employees, we identify high exposures to particulate matter and, carbon monoxide in addition to self-reported respiratory symptoms.